Struktur Modal dan Keputusan Investasi Terhadap Nilai Perusahaan - Monica, Lara; Muchdie, Muchdie; Achmadi, Uzair (Agregat: Jurnal Ekonomi dan Bisnis, 2017)
The purpose of this research is to analyze and determine whether there is a direct effect of capital structure (X1) and the Investment Decision (X2) the Value of the Company (X3) at the companys advertising, printing and media in the Indonesian Stock Exchange. The population in this research is 14 companies. Samples are 9 companies with purposive sampling method. This type of research is quantitative. Analysis of data use path analysis with SPSS 21. Based on data analysis, the results show that the capital structure (X1) has significant negative direct impact to investment decisions (X2), the capital structure (X1) has no direct impact significantly on company value (X3), the investment decision (X2) has significant positive direct impact to company value (X3) and capital structure (X1) has significant negative direct impact to company value (X3) through investment decisions (X2).